Equity and efficiency in multi-worker firms: Insights from experimental economics - Johannes Abeler; Steffen Altmann; Sebastian J. Goerg; Sebastian Kube; Matthias Wibral (Institute for the Study of Labor (IZA), 2011)
In this paper, we discuss recent evidence from economic experiments that study the impact of social preferences on workplace behavior. We focus on situations in which a single employer interacts with multiple employees. Traditionally, equity and efficiency have been seen as opposing aims in such work environments: individual pay-for-performance schemes maximize efficiency but might lead to inequitable outcomes. We present findings from laboratory experiments that show under which circumstances partially incomplete contracts can create equitable work environments while at the same time reaching surprisingly efficient outcomes.
urn:nbn:de:101:1-201106013413
Keywords: J33; D63; M52; C92; J41; 330; incentives; wage setting; equity; gift exchange; reciprocity; incomplete contracts; organizational economics; laboratory experiments